Atlas of blood pathology - Ward, Patrick C. J.; Chapman and Hall (New York : Chapman & Hall, 1997)
Covers 144 disease entities and 200 diagnostic features, including 9762 high resolution color images, with accompanying descriptions. Information can be accessed by disease and by feature. Lectures and references are also available
Disc 1. Anemias -- Disc 2. Lymphoid & misc. disorders -- Disc 3. Myeloid disorders
Title from disc label; date from insert
System requirements: Power Mac, 50 MHz (66 or > MHz recommended); 8 MB RAM; 5 MB free hard disc space; double-speed CD-ROM drive or better; 16-bit color (640 X 480 pixel) SVGA (24-bit color recommended)
System requirements: PC with 486SX processor, 50 MHz (66 or > MHz recommended); 8 MB RAM; 5 MB free hard disc space; double-speed CD-ROM drive or better; 16-bit color (640 X 480 pixel) SVGA (24-bit color recommended)
Keywords: Hematologic Diseases -- pathology -- atlases; Blood Cells -- pathology -- atlases